Sprinting tips - Whitten, T.; Crawford, C. (2007)
It`s time to get race-ready. It`s time to gather the threads of hard training and things learned from the summer, and weave them into a super strong rope that you can trust like it is supporting your life on a huge cliff face… or use it to lasso Beckie Scott in the next sprint race and hang on for dear life! Let`s call the latter option "plan B" and instead focus on the things we need to do well to race as fast as possible come race day. Below is a not-so-brief compilation of some of the things that are important to my teammate Tara and I in training and racing. The emphasis is on sprint racing, but you can see how putting these ideas into action could improve your distance races as well.